Simulation of moisture content in alpine rockwalls during freeze–thaw events. Issue 13 (6th October 2016) - Rode, Matthias; Schnepfleitner, Harald; Sass, Oliver
Abstract: Rock moisture during freeze–thaw events is a key factor for frost weathering. Data on moisture levels of natural rockwalls are scarce and difficult to obtain. To close this gap, we can benefit from the extensive knowledge of moisture‐related phenomena in building materials, which is incorporated into simulation software, for example the WUFI® package of the Fraunhofer Institute of Building Physics. In this paper we applied and adapted this type of simulation to natural rockwalls to gain new insights on which moisture‐related weathering mechanisms may be important under which conditions. We collected the required input data on physical rock properties and local climate for two study areas in the eastern European Alps with different elevation [Sonnblick, 3106 m above sea level (a.s.l.) and Johnsbach, 700 m a.s.l.] and different lithologies (gneiss and dolomite, respectively). From this data, moisture profiles with depth and fluctuations in the course of a typical year were calculated. The results were cross‐checked with different thermal conditions for frost weathering reported in the literature (volumetric expansion and ice segregation theories). The analyses show that in both study areas the thresholds for frost cracking by volumetric expansion of ice (90% pore saturation, temperature < −1 °C) are hardly ever reached (in one year only 0.07% of the time in Johnsbach and 0.4% at Sonnblick, mostly in north‐exposed walls). The preconditions for weathering by ice segregation (−3 to −8 °C, > 60% saturation) prevail over much longer periods; the time spent within this 'frost cracking window' is also higher for north‐facing sites. The influence of current climate warming will reduce effective frost events towards 2100; however the increase of liquid precipitation and rock moisture will promote weathering processes like ice segregation at least at the Sonnblick site. Copyright © 2016 John Wiley & Sons, Ltd.